Higher Education in the Age of Populism: Public Good and Civic Engagement - Hazelkorn, Ellen (International Higher Education, 2020)
The last few years have been a rude awakening for higher education. Rising frustration with the unequal distribution of globalization’s benefits and growing disparities between urban centers and their rural hinterlands has given way to the age of populism. Universities have become caught up in this polarizing battle, too often seen as centers of privilege and elites disengaged from the publics that host and fund them, rather than upholding the public good. Today’s challenges mean the university cannot sit on the sidelines—nor can its students. There is a lot at stake. Is civic engagement the path to regaining public trust?